Combination therapy of low-dose radiotherapy and immunotherapy in advanced metastatic nasopharyngeal carcinoma: a case report and literature review - Chun-Qiao Chen; Hui Huang; Min Pan; Zhe Jia; Jing Zhang; Qiu-Qiu Chen (Discover Oncology)
Abstract Background Nasopharyngeal cancer (NPC) is a common head and neck malignant tumor, which is difficult to treat at the advanced NPC due to its occult and high metastatic potential to the cervical lymph nodes and distant organs. Low-dose radiotherapy (LDRT) is increasingly being investigated for potential cancer treatment. When combined with immune checkpoint inhibitors, LDRT has been shown to significantly improve the immune microenvironment of tumors, thereby promote the immune attack on tumor cells. However, the therapeutic effect of LDRT combined with immunotherapy in advanced NPC is not well understood. Case summary We report a case of a 31-year-old man was diagnosed with advanced metastatic nasopharnygeal non-keratinizing carcinoma (T4N3M1 stage IVb AJCC8th). The patient was treated with a high-dose of radiation therapy combined with LDRT and immunotherapy to inhibit tumor cell proliferation and activate the body's immune system. The initial treatment procedure was as follows: chemotherapy regimen (nedaplatin + docetaxel + fluorouracil) induction, followed by radical radiotherapy for the primary lesion, LDRT for the L5 vertebral body metastasis, and concurrent use of low-dose capecitabine beat chemotherapy and toripalimab immunotherapy. The patient was also administered with human granulocyte–macrophage colony-stimulating factor and aspirin to enhance the immune function. This combination therapy approach alleviated patient symptoms, improved bone changes in the L5 vertebral body and resolved the tumor without any adverse effects signals. The progression-free survival (PFS) has reached 27 months and he is currently stable without tumor recurrence. Conclusion The combination of chemotherapy and LDRT with aspirin and human granulocyte macrophage colony-stimulating factor improved the disease state of advanced NPC cancer, effectively reducing the level of tumor markers, enhanced the immune function without significant adverse reactions.